Sufi interpretation in Islam: History, limitations, influences, and criticisms - Saufa, Syifa Nur; Shofiyah, Siti (UIN Sunan Gunung Djati Bandung, 2025)
In every era, the interpretation of the Qur'an reflects a diversity of approaches, depending on the scholarly expertise of the interpreters (mufassir). One distinctive interpretative pattern is Sufi exegesis, despite its limited development due to challenging sceptical views. This research aims to address inquiries regarding the scope of Sufi exegesis, encompassing its historical emergence, limitations, differences in scholars' perspectives, and the terms